Mediation as an alternative method of solving disputes in intellectual property - Троцюк, Ніна Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article is dedicated to research of general principles of mediation as an alternative method of solving disputes regarding intellectual property rights in Ukraine. Defined the concept, purpose, characteristics and types of mediation. Analyzed the modern state of the legal regulation of mediation in Ukraine and mediation procedures in national law of the member states of the European Union. Dynamic development of the information society has set in front of the legal science a number of challenges related, first of all, to protection of rights of the patents holders from patent trolling, copyright protection on Internet, proper operation of collective management of authors` property rights, application of alternative procedures for resolving disputes concerning intellectual property etc. Particularly worth to be mentioned is the issue of alternative resolving of disputes concerning intellectual property items within the framework of mediation. Alternative disputes resolving is the general term used to define a set of approaches and methods, aimed at conflict-free disputes resolving, starting from negotiations in-between the parties, multilateral negotiations, mediation, consensus finding and arbitration. The aim of the article is to analyze specifics of mediation application to disputes related to items of intellectual property. It is determined that one of the directions of reforming the system of intellectual property protection is application of mediation mechanisms in the sphere of intellectual property. Quite a lot was done in Ukraine towards this. On November 1st, 2016 the draft law “On mediation” was voted for in the first reading. The draft law defines the legal framework for rendering mediation services on professional basis and is aimed at introduction of mediation institute in the society, extending the practice of amicable disputes resolving through out-of-court settlement and ensuring balanced relations between the institute of mediation and the court system. According to Art. 3 of the draft law, mediation can be applied to any conflicts (disputes) including civil, family, labour, economic, administrative as well as criminal proceedings and cases of administrative offences. It is determined that in the European Union countries mediation as the way of resolving the dispute (conflict) resulting from any legal relations (family, labour, economic, civil etc.) is used much more often as compared to other out-of-court alternative methods of disputes solving, as for example, negotiations, conciliation, mini-process, pre-trial conference or simplified jury trial. Having analyzed the European experience of establishing and applying the procedure of mediation as an alternative method of disputes resolving in numerous areas of public relations, including intellectual property, we believe that the forthcoming law of Ukraine “On Mediation” will promote the culture of amicable disputes resolving in the society, will enable mediation to be the best alternative to litigation. However, to ensure proper functioning of this institute in Ukraine, it is necessary to train qualified specialists, having not only professional knowledge, but also psychological skills to resolve the disputes. On a separate note, attention should be paid to the issue of improving the legal literacy of the future mediators and arrangement of the relevant campaign in the mass media, social networks which will inform the citizens about this institute, its advantages and application features.